2022
DOI: 10.3390/jfb13020074
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of 3D-Printed Silica-Based Bioactive Glass Scaffolds for Bone Regeneration

Abstract: Bioactive glasses are often designed as porous implantable templates in which newly-formed bone can grow in three dimensions (3D). This research work aims to investigate the bone regenerative capability of silicate bioactive glass scaffolds produced by robocasting in comparison with powder and granule-like materials (oxide system: 47.5SiO2-10Na2O-10K2O-10MgO-20CaO-2.5P2O5, mol.%). Morphological and compositional analyses performed by scanning electron microscopy (SEM), combined with energy dispersive spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Cracking ( Figure 8 a,c) was the result of vacuum dehydration during sputter-coating prior to SEM analysis. After 7 days of immersion in SBF, EDS analysis revealed a Ca-to-P ratio of about 1.5 (atomic ratio), which is typical of the Ca-deficient hydroxyapatite formed on the surface of bioactive silicate glasses of various compositions [ 30 , 31 , 32 , 33 ]. A comparable Ca-to-P ratio was also found on the surface of robocast 47.5B scaffolds also soaked in SBF for 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…Cracking ( Figure 8 a,c) was the result of vacuum dehydration during sputter-coating prior to SEM analysis. After 7 days of immersion in SBF, EDS analysis revealed a Ca-to-P ratio of about 1.5 (atomic ratio), which is typical of the Ca-deficient hydroxyapatite formed on the surface of bioactive silicate glasses of various compositions [ 30 , 31 , 32 , 33 ]. A comparable Ca-to-P ratio was also found on the surface of robocast 47.5B scaffolds also soaked in SBF for 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…An apatite-rich layer (cauliflower-like apatite) on the surface of the scaffolds formed more substantially on the surface of the Zn-Sr-BGNP: Alg composite scaffolds after soaking in the SBF solution for 21 days than on the alginate scaffolds. The formation of this apatite layer helped recruit cells to the scaffold and assisted with the cell attachment [ 28 , 36 ]. EDX analysis was conducted to determine the chemical composition of the mineral seen in the SEM images.…”
Section: Resultsmentioning
confidence: 99%
“…BG can be used as a raw material for a variety of 3D printing techniques, including SLS, SLA, and FDM [ 171 ]. Tulyaganov et al demonstrated the effectiveness of 3D-printed silica-based BG in forming hydroxyapatite within simulated body fluid (SBF), as well as an in vivo 4.5 mm rabbit femoral defect model, in which the 3D-printed BG scaffolds resulted in osseous defect healing and the formation of new bone [ 172 ].…”
Section: Future Directions For Addressing Bone Lossmentioning
confidence: 99%